MOBILE INDOOR AND OUTDOOR LOCALIZATION AND GUIDANCE SYSTEM USING AUGMENTED REALITY - JHEI XERN, ANG (2018)
As technology advances, humans begin to be more dependent on the new technologies and rely on them more often. Various stuff which were deemed difficult in the past can be easily solved following the advancement of technologies. One of the issues that can be solved with the advancement of technology is the ability to locate oneself. Back in the old days, humans heavily rely on items such as compasses and paper maps to vaguely guess the location they were on. These items can be deemed inaccurate as they are all based on the user’s intuition and perspective, hence there is no definitive way to correctly determine their location. This issue can be solved with the advancement of technology. Nowadays, we can easily determine our location with only a single click of a button using our mobile devices. This is done by utilizing the Global Positioning Signal (GPS), which obtains the user’s location using satellite. At indoor location, the GPS signals can be blocked by concrete walls, hence an alternate solution has to be in place for such scenarios. For this project, the aim is to combine various methods so that we are able to track the user’s location at both an indoor and outdoor environment. For indoor location, QR codes are utilized as a solution to weak GPS signals. Augmented Reality (AR) system is utilized to make the application more user-friendly and easier for the user to understand. The various sensors in a mobile device are also utilized to count the number of steps the user had taken in order to predict the number of steps left for the user to reach the destination.